2020
DOI: 10.1111/jcmm.15803
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of berberine on the inflamed joint reveal new therapeutic targets for rheumatoid arthritis management

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 130 publications
2
24
0
Order By: Relevance
“… 49 The absence of increased cell death in our experimental assay is consistent with the reported chondroprotective influence of BBR, 44 and supports the specificity of the dying influence of BBR on different cell lineages. As reported in different experimental studies, 22 , 48 , 50 we have observed a mild, but significant, transcriptional influence of BBR on genes associated with cell death and developmental cell senescence, 51 , 52 including p21 and Bak1, p53 and the tumor suppressor gene Btg1 . This moderate gene up-regulation in our in vitro assay appeared insufficient to induce apoptosis or increased SAβ-gal activity in early or late cultures at the end of the 6 hr period of treatment.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“… 49 The absence of increased cell death in our experimental assay is consistent with the reported chondroprotective influence of BBR, 44 and supports the specificity of the dying influence of BBR on different cell lineages. As reported in different experimental studies, 22 , 48 , 50 we have observed a mild, but significant, transcriptional influence of BBR on genes associated with cell death and developmental cell senescence, 51 , 52 including p21 and Bak1, p53 and the tumor suppressor gene Btg1 . This moderate gene up-regulation in our in vitro assay appeared insufficient to induce apoptosis or increased SAβ-gal activity in early or late cultures at the end of the 6 hr period of treatment.…”
Section: Discussionsupporting
confidence: 81%
“…The increased chondrogenesis observed after treatments of cultures at advanced stages of cartilage differentiation might be important when considering the therapeutic influence of BBR on joint cartilage degeneration. 22 In our experimental model, BBR at initial stages of culture inhibited chondrogenesis, up-regulating pro-fibrogenic genes ( Tgfβ2 and Scleraxis ) but not Sox9 , and maintained progenitors into a fibroblastic-like state. However, the addition of BBR to the culture medium at advanced stages of culture promoted chondrogenesis, deduced by the intensification of Alcian blue specific cartilage staining and by the transcriptional up-regulation of Sox9 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Berberine inhibits in ammatory proliferation of synovial cells, suppresses DC activation, regulates Th17/Treg balance, and prevents cartilage and bone destruction by regulating various signaling pathways involved in in ammatory responses, including PI3K/Akt. Such molecular targets may explore new RA treatment targets [60].…”
Section: Discussionmentioning
confidence: 99%
“…In regard to RA specifically, BBR has been successful at treating clinically apparent CIA and other RA animal models in vivo through a number of suggested mechanisms, such as (a) dendritic cell apoptosis [24], (b) interference with MAPK signaling via inhibition of p-ERK, p-38, and p-JNK [25,32], (c) attenuation of T h 17 activity via inducing cortistatin in the gut [27], (d) restoration of the balance between T reg /T h 17 cells [26], (e) the suppression of T h 17 differentiation/proliferation through inhibition of CD169 and the RORγt transcription factor, (f) induction of T reg differentiation through aryl hydrocarbon receptor (AhR) activation [33], (g) and promotion of anti-inflammatory M2 macrophage polarization through upregulation of p-AMPK and inhibition of HIF1α [34]. A more detailed account of the anti-inflammatory actions of BBR in the context of rheumatoid arthritis can be found in the recent review by Shen et al (2020) [35].…”
Section: Introductionmentioning
confidence: 99%